COMPARATIVE PERFORMANCE OF BIVOLTINE FOUNDATION CROSSES TO BE USED AS MALE COMPONENTS FOR PRODUCTION OF MULTI x BI DFLs - CHANDA, S.; SAHA, L. M.; SINGH, W. S.; KUMAR, S. NIRMAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Reproductive parameters viz., pupal survival percentage, pairing efficiency, recovery of disease free layings both in number and by weight, number of eggs per gram, fecundity and hatching percentage were studied among the Multix Bi combinations of M.Con.4 and M6D(P)C with four bivoltine foundation crosses (FCs) viz.: [D6(P)N X SK4(C)), (Gen3 x BHR2),(B.Con.4 x B.Con. 1) and (SK6 x SK7) which were used as source of male components. Pupal survival percentage >70% in case of all of the bivoltine FC breeds during the most unfavourable season (July-Aug.) of eastern part of India assures that foundation crosses can be reared in unfavourable seasons in tropical zones of India. Significant variation (P<0.05) in recovery both in percentage and weight among all combinations of M.Con.4 and M6D(P)C with males moths of D6(P)N X SK4C), (Gen3 X BHR2), (B.Con.4 x B.Con. 1) and (SK6 X SK7) were perceived during this study. Number of eggs per gram also showed significant difference (P<0.05) among different crosses. Evaluation of all reproductive parameters were conducted by following Mano's Evaluation Index and it has been observed that D6(P)N X SK4C) can be considered as the source of most competent male moths for production of Multix Bi eggs under high temperature and high humidity conditions. The males of B.Con.4 x B.Con. 1 can be utilized as second option for production of quality Multix Bi DFLs in combination with females of multivoltine breed, M6D(P)C under high temperature and high humidity condition.